A G20 Facility to rekindle FDI flows - Karl P. Sauvant (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2020)
The G20 should establish an FDI Facility as part of a spare-no-effort response to the economic impact of the pandemic and to help accelerate sustainable FDI flows for sustainable development.
Keywords: 330